1989
DOI: 10.1093/ajcp/92.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial Fine-Needle Aspiration: Reliability and Limitations

Abstract: Transbronchial needle aspiration is a new method of sampling pulmonary, paratracheal, and mediastinal masses. A total of 116 aspirations of the lung performed during a two-and-a-half-year period were reviewed. The results were compared with those of bronchial wash, bronchial brush, sputum, transbronchial forceps biopsy, and histologic material subsequently obtained during surgery or at autopsy. Clinical information was also reviewed. Transbronchial needle aspiration was performed on 104 patients, yielding 116 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…urinary tract and distal respiratory airways). In general, in the presence of a tumor mass, FNA is more sensitive than lavage/wash in detecting malignancy, 8 and the results of our study indicate that this is also true with regard to the breast. Because of intrinsic differences in the two techniques, DL and FNA of the breast apply to different clinical scenarios and either one or the other should be chosen based on the clinical setting.…”
Section: Discussionsupporting
confidence: 58%
“…urinary tract and distal respiratory airways). In general, in the presence of a tumor mass, FNA is more sensitive than lavage/wash in detecting malignancy, 8 and the results of our study indicate that this is also true with regard to the breast. Because of intrinsic differences in the two techniques, DL and FNA of the breast apply to different clinical scenarios and either one or the other should be chosen based on the clinical setting.…”
Section: Discussionsupporting
confidence: 58%
“…According to previous findings, false negative results on cytology ranged from 5% to 65% [5][6][7]9,10,[14][15][16][17]19]. This wide variability in cytological yield among studies can be related to several factors, such as size of the study population, the cytological procedure being employed, and quality of specimens, location and size of the lung tumour, endoscopic findings, as well as the investigational procedure regarded as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological procedures are often employed, as they are less invasive and easier to perform, but their accuracy with regard to lung cancer cell type has been previously questioned [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Payne et al have reported an overall diagnostic accuracy achieved by sputum cytology, bronchial aspirates, and bronchial biopsies of 89%, 86% and 92%, respectively, when compared to histology of resected tumour or necropsy specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, mediastinoscopy and thoracoscopy have been considered as the reference standards for sampling mediastinal lymph nodes, but such methods are invasive, expensive, and require general anesthesia and hospital admission [1]. Actually, there is increasing evidence that transbronchial needle aspiration (TBNA) of the mediastinal lymph nodes under direct realtime endobronchial ultrasound (EBUS) guidance is a safe and useful means of obtaining biopsy specimens from these nodes in lung cancer patients [2][3][4][5]. In addition, cases of mediastinal lymph node metastases from extrathoracic malignancy diagnosed by EBUS TBNA have been reported [6].…”
Section: Introductionmentioning
confidence: 99%